Types of social capital resources and self-rated health among the Norwegian adult population - Gele Abdi A; Harsløf Ivan (BMC, 2010)
Abstract Background Social inequalities in health are large in Norway. In part, these inequalities may stem from differences in access to supportive social networks - since occupying disadvantaged positions in affluent societies has been associated with disposing poor network resources. Research has demonstrated that social networks are fundamental resources in the prevention of mental and physical illness. However, to determine potentials for public health action one needs to explore the health impact of different types of network resources and analyze if the association between socioeconomic position and self-rated health is partially explained by social network factors. That is the aim of this paper. Methods Cross-sectional data were collected in 2007, through a postal survey from a gross sample of 8000 Norwegian adults, of which 3,190 (about 40%) responded. The outcome variable was self-rated health. Our main explanatory variables were indicators of socioeconomic positions and social capital indicators that was measured by different indicators that were grouped under 'bonding', 'bridging' and 'linking' social capital. Demographic data were collected for statistical control. Generalized ordered logistic regression analysis was performed. Result Results indicated that those who had someone to talk to when distressed were more likely to rate their health as good compared to those deprived of such person(s) (OR: 2.17, 95% CI: 1.55, 3.02). Similarly, those who were active members in two or more social organisations (OR: 1.73, 95% CI: 1.34, 2.22) and those who count a medical doctor among their friends (OR: 1.51, 95% CI: 1.13, 2.00) report better health. The association between self-rated health and socio-economic background indicators were marginally attenuated when social network indicators were added into the model. Conclusion Among different types of network resources, close and strong friendship-based ties are of importance for people's health in Norway. Networks linking people to high-educated persons are also of importance. Measures aiming at strengthening these types of network resources for socially disadvantaged groups might reduce social inequalities in health.